Analisis Estimasi Pengiriman dan Kualitas Packaging: Studi Kasus PT. Lion Parcel Cabang Krakatau - Harahap, Ella Anderina; Syauqi, Teuku Muhammad; UTU, Rusdi; Anwar, Saiful (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
This study aims to analyze the effect of delivery estimates and packaging on consumer decisions in using the services of PT Lion Parcel Krakatau Branch in Medan. The research method used is quantitative, with data collection techniques through questionnaires, interviews, and documentation. The research sample of 94 respondents was determined using the Slovin formula. Data analysis was carried out through multiple linear regression tests and hypothesis testing. The results showed that the shipping estimate (X1) has a tcount value of 6.819> ttable 1.661 with a significance of 0.000 <0.05, so it has a significant effect on consumer decisions. Packaging (X2) also shows a significant effect with a tcount of 6.164> ttable 1.661 and a significance of 0.000 <0.05. Simultaneously, the F test shows Fcount 95.453> Ftable 3.10 with a significance of 0.000 <0.05, which means that these two variables jointly influence consumer decisions. The R Square value of 0.677 indicates that shipping and packaging estimates affect consumer decisions by 67.7%, while 32.3% is influenced by other factors. This research contributes to providing insights for the logistics industry, where improving the accuracy of shipping estimates and packaging quality can increase customer satisfaction and loyalty.